URBAN FORM AS A TOOL FOR VALIDATING THE QUALITY OF LIFEIN URBAN PRECINCTS - VINODH VIJAYAKUMAR, SANGEETHA SP (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The intent of any planning or urban design exercise is to increase the quality of living conditions of inhabitants alongside providing aesthetically pleasing and effectively serviced neighbourhoods. The Quality of Living in a neighbourhood arises out of the synthesis of a various attributes which influence the living conditions of an individual in a neighboorhood. Certain neighbourhoods seemingly appear more structured and planned than the others. This study attempts to quantify the various aspects of the neighbourhood and built environment that improves the quality of living of the individual. This study also attempts to validate the significance of a planned and organized urban form on its positive impacts on its inhabitants and its contribution to the overall quality of living in the environment.